2006
DOI: 10.1111/j.1365-2419.2005.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention mechanisms of white perch (Morone americana) and striped bass (Morone saxatilis) early‐life stages in an estuarine turbidity maximum: an integrative fixed‐location and mapping approach

Abstract: The small-scale distribution and retention mechanisms of white perch (Morone americana) and striped bass (M. saxatilis) early-life stages were investigated in the upper Chesapeake Bay estuarine turbidity maximum (ETM). Physical measurements and biological collections were made at fixed-location stations within the ETM during three research cruises in 1998 and two in 1999. Results were compared with mapping surveys of physical properties and organism distributions above, within, and below the ETM. Physical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…It was hypothesized that freshwater flow controls recruitment by its effect on the overlap of temperature/salinity zones preferred by larvae and the elevated secondary productivity in the ETM (North & Houde 2006). Our results are generally consistent with this hypothesis, although we found that distributions of larval striped bass are not closely coupled to the ETM in all years.…”
Section: The Etm and Recruitment Successsupporting
confidence: 82%
See 1 more Smart Citation
“…It was hypothesized that freshwater flow controls recruitment by its effect on the overlap of temperature/salinity zones preferred by larvae and the elevated secondary productivity in the ETM (North & Houde 2006). Our results are generally consistent with this hypothesis, although we found that distributions of larval striped bass are not closely coupled to the ETM in all years.…”
Section: The Etm and Recruitment Successsupporting
confidence: 82%
“…Frontal features, in general, enhance prey availability, feeding success, or growth of marine and estuarine fish The ETM in Chesapeake Bay appears to support retention and high production of zooplankton eaten by striped bass larvae (Roman et al 2001, North & Houde 2006. High freshwater flows increase estuarine gravitational circulation (Hetland & Geyer 2004) and may favor higher zooplankton production in addition to retention of particles, including detritus, zooplankton, and larval fish at the salt front and ETM.…”
Section: The Etm and Recruitment Successmentioning
confidence: 99%
“…Understanding the relative importance of auto chthonous algal production compared to allochthonous input in the ETM is particularly important because this region is an area of high larval recruitment for many fish species including striped bass Morone saxatilis and white perch M. americana (North & Houde 2006). Mesozooplankton such as the calanoid copepods Eurytemora affinis and Acartia tonsa and the freshwater cladoceran Bosmina longirostris are also very abundant (Roman et al 2001).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…In lakes, stable isotope analysis of organic carbon indicates that a greater fraction of heterotrophic metabolism is fueled by terrestrial organic matter than by autochthonous primary producers when environmental conditions limit autotrophic production (Carpenter et al 2005, Pace et al 2007). In Chesapeake Bay, primary production and chlorophyll a (chl a) concentrations are lowest in the oligohaline area (Smith & Kemp 1995), presumably due to light limitation (Fisher et al 1999), suggesting that, as in lakes, terrestrial organic matter plays an important role in heterotrophic production.Understanding the relative importance of auto chthonous algal production compared to allochthonous input in the ETM is particularly important because this region is an area of high larval recruitment for many fish species including striped bass Morone saxatilis and white perch M. americana (North & Houde 2006). Mesozooplankton such as the calanoid copepods Eurytemora affinis and Acartia tonsa and the freshwater cladoceran Bosmina longirostris are also very abundant (Roman et al 2001).…”
mentioning
confidence: 99%
“…Stable isotope studies indicate that estuarine food webs are supported by inputs of freshwater and terrestrial sources of nutrients and organic matter (Kostecki et al, 2010). It is assumed that discharge effects on estuarine hydrodynamics and nutrient transport ultimately concentrate high secondary production of zooplankton in estuarine regions where fresher and saltier waters converge (North and Houde, 2006;Baptista et al, 2010). These mechanisms are thought to produce a dome-shaped relationship between estuarine fi sh production and freshwater discharge (Dolbeth et al, 2010; and references therein).…”
Section: Figurementioning
confidence: 99%